mTOR signaling-related MicroRNAs and Cancer involvement - WANG, Ping (J Cancer, 2018)
MicroRNAs (miRNAs) are a class of single-stranded RNAs, 18-23 nucleotides in length that regulate gene expression at the post-transcriptional level. Dysregulation of miRNAs has been closely associated with the development of cancer. In the process of tumorigenesis, mammalian target of rapamycin (mTOR) plays important roles, and the mTOR signaling pathway is aberrant in various types of human cancers, including non-small cell lung cancer (NSCLC), breast cancer, prostate cancer, as well as others. However, the relationship between miRNAs and the mTOR signaling pathway is indistinct. Herein, we not only summarize the progress of miRNAs and the mTOR signaling pathway in cancers, but also highlight their role in the diagnosis and treatment in the clinic.